A frequency reconfigurable antenna with Bluetooth, Wi-Fi and WLAN notch band characteristics - Vamseekrishna, A; T P Madhav, B (International Journal of Engineering and Technology, 2018)
A compact coplanar waveguide fed reconfigurable antenna with three notch bands are presented in this paper. Proposed antenna reconfigurability is acquired by placing bar6404 PIN diodes in the S-shaped ground plane in right to left mode and left to right mode. By switching the diode, reconfigurability achieved for three different operations. The substrate material for the proposed antenna is FR4 with dielectric constant 4.4 and loss tangent 0.02. The overall dimension of the reconfigurable antenna is around 30Ã—26mm2. It is being observed in this work for the cause of each individual slot on notch band characteristics. The measured gain for the designed reconfigurable antenna is quite stable at operating frequencies except notch bands. The proposed antenna is suitable for practical wideband applications with notching.